Barriers and Facilitators of Using Standardized Outcome Measures in Stroke Rehabilitation in Saudi Arabia: A Cross-Sectional Study of Practice Among Neuropysiotherapists - Alhwoaimel NA; Alqahtani BA; Alhowimel AS; Alshehri MM; Alhelal AK; Al-assaf LG; Alenazi AM (Dove Medical Press, 2024)
Norah A Alhwoaimel,1 Bader A Alqahtani,1 Ahmed S Alhowimel,1 Mohammed M Alshehri,2 Afrah K Alhelal,1 Lujain G Al-assaf,1 Aqeel M Alenazi1 1Department of Health and Rehabilitation Sciences, Prince Sattam Bin Abdulaziz University, Al-kharj, 11942, Saudi Arabia; 2Department of Physical Therapy, Jazan University, Jazan, 45142, Saudi ArabiaCorrespondence: Mohammed M Alshehri, Department of Physical Therapy, Jazan University, Jazan, 45142, Saudi Arabia, Email moalshehehri@jazanu.edu.saBackground: Clinical guidelines emphasize the use of standardized outcome measures (SOMs) in post-stroke rehabilitation. However, the extent of SOM utilization among physiotherapists in this context in Saudi Arabia remains unclear.Aim: 1) assess the current use of SOMs by physiotherapists involved in stroke rehabilitation in Saudi Arabia and 2) identify facilitators and barriers influencing the use of SOMs.Methods: An online survey was administered using a three-section questionnaire designed for this study. The first section collected demographic data, the second evaluated the use of SOMs recommended by the American Physical Therapy Association, and the third explored factors facilitating or hindering SOM use in clinical practice. Only highly recommended outcome measures capturing the three levels of the International Classification of Functioning, and Disability (ICF) model were considered: body structure and function, activities, and participation. Poisson regression analysis was used to investigate the association between SOMs utilization and educational level, work experience, type of work facility, and the number of patients treated per week.Results: A total of 138 physiotherapists responded. Most participants (98.5%) used at least one outcome measure in clinical practice. Regression analysis showed that number of strokes treated per week and facility type were associated with the likelihood of using higher number of SOMs. Physiotherapists managing more than 10 stroke patients per week and working in private sector had significantly higher odds of using a greater number of SOMs. The most pronounced barriers were time restrictions and limited resources.Conclusion: Physiotherapists working with stroke patients in Saudi Arabia demonstrate a high awareness and positive attitude toward SOM utilization. Addressing barriers such as time management and resource allocation is crucial to enhancing SOM integration in clinical practice.Clinical Rehabilitation Impact: Organizational support in terms of adequate time and resources is needed to enhance the use of SOMs among physiotherapists.Keywords: outcome measure, outcome assessment, neurorehabilitation, rehabilitation, neurophysiotherapy